PENGEMBANGAN PEMBELAJARAN E-LEARNING BERBASIS MEDIA SOSIAL DALAM MENINGKATKAN KOMPETENSI PENDIDIKAN KEWARGANEGARAAN - Inggis Mialiawati; Yusuf Yusuf (Widya Wacana: Jurnal Ilmiah, 2021)
Civic education learning at this time only covers the cognitive domain, even though there are three (3) domains that must be met, namely cognitive, affective, psychomotor. There is a need for the development of technology and information, one of which is e-learning. E-learning is a learning model that is created in digital format through an electronic device. The purpose of writing this scientific article is to develop social media based e-learning in impoving civic education competency. Writing this article uses descriptive analytical methods, data collection, and data analysis. The result of the discussion : the use of social media such as Blog, Twitter, Facebook, Instagram, Path, dan Wikipedia is very helpfulin developing learning to improve civic education competence to discuss, interact, explore exisiting problems in society to move the sorrunding community to learning resources that can be accessed by social media so that they are connected to the global world.